2017
DOI: 10.3390/ijms18081761
|View full text |Cite
|
Sign up to set email alerts
|

Licochalcone A Inhibits the Proliferation of Human Lung Cancer Cell Lines A549 and H460 by Inducing G2/M Cell Cycle Arrest and ER Stress

Abstract: Licochalcone A (LicA), a flavonoid isolated from the famous Chinese medicinal herb Glycyrrhiza uralensis Fisch, has wide spectrum of pharmacological activities. In this study, the anti-cancer effects and potential mechanisms of LicA in non-small cell lung cancer (NSCLC) cells were studied. LicA decreased cell viability and induced apoptosis in a dose-dependent manner in NSCLC cells. LicA inhibited lung cancer cells growth by blocking cell cycle progression at the G2/M transition and inducing apoptosis. LicA tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 34 publications
4
61
1
Order By: Relevance
“…LCD decreased cyclin B1/cdc2 protein expression but increased CKI, causing G2/M cell cycle arrest. LCA and LCB of the same licorice family as LCD can also block G2/M cell cycle progression and induce the apoptosis of lung cancer cells [14,24]. Some agents that can induce apoptosis may also increase cytotoxicity in association with G2/M checkpoint arrest [23].…”
Section: Discussionmentioning
confidence: 99%
“…LCD decreased cyclin B1/cdc2 protein expression but increased CKI, causing G2/M cell cycle arrest. LCA and LCB of the same licorice family as LCD can also block G2/M cell cycle progression and induce the apoptosis of lung cancer cells [14,24]. Some agents that can induce apoptosis may also increase cytotoxicity in association with G2/M checkpoint arrest [23].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the core of the cell cycle regulation mechanism is a group of cell cycle dependent protein kinase (CDKs), which is dependent on their regulatory subunit cyclins. Cyclin E and CDK2 are major regulators of cell cycle checkpoint and their interaction triggers the entry into the S phase, while cyclin B1‐CDK1 is potential to promote cell cycle progression from the S phase to G 2 /M phase . ADP has been reported to inhibit proliferation of the human lung adenocarcinoma cells via the induction of massive accumulation of cells in the S phase .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that licorice roots contain multiple bioactive components such as saponins, flavonoids, and coumarins [13][14][15]. Furthermore, licorice has been shown to have anticancer effects in various types of cancer such as colon [16], lung [17,18], breast [19,20], prostate [21], and oral cancers [11] through metastatic inhibition [19], anti-proliferative properties [20], increased apoptosis [11,22], and cell cycle arrest [23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies have also reported reduction in chronic allergic contact dermatitis as well as antidiabetic, anti-inflammatory, and antimicrobial effects. Anticancer effects of Lico-A have been prominently reported for various types of cancers, such as A549 and H460 human lung cancer cells [17], T24 bladder cancer cells [31], human cervical cancer cells [32], human BGC-823 gastric cancer cells [33], malignant pleural mesothelioma [34], human FaDu head and neck squamous carcinoma cells [22], and human esophageal carcinoma [35] among others. On the other hand, although recent studies associated with the biological effects of Lico-E have been reported antidiabetic effect [36], the reduction of chronic allergic contact dermatitis [37], neuronal protection [38], anti-inflammation [39] and antimicrobial effects [40], but the anticancer effects of Lico-E reported in the 4T1 mammary orthotopic cancer [41] and human head and neck squamous carcinoma FaDu cells [11].…”
Section: Discussionmentioning
confidence: 99%